Causes of Illegal Gold Mining - Sarmadan Pohan; Alvi Syahrin; Edi Yunara; Mohammad Ekaputra; Rosmalinda Rosmalinda (International Conference on Economic Business and Social Science, 2025)
The sovereignty over natural resources in Indonesia faces challenges due to foreign corporate ownership, which can undermine national control over these resources (Cotula, 2016). Article 33 of the 1945 Constitution, however, asserts that the management of these resources must prioritize the welfare of the people and be under state control (Miranda, 2012). Illegal mining activities, particularly in Mandailing Natal Regency, have become a serious concern, as they are carried out without proper government permits and contribute to significant environmental degradation (Jacob & Gunadi, 2023). This study aims to examine the factors contributing to illegal mining in the region and the effectiveness of current policies aimed at curbing these activities. Using qualitative methods, including interviews with local miners, this research explores the economic, social, and legal aspects influencing illegal mining. The findings indicate that economic factors, lack of socialization about legal mining regulations, and weak law enforcement are the primary drivers behind illegal mining. The study suggests that raising public awareness and strengthening legal frameworks could significantly mitigate illegal mining activities. Ultimately, this research contributes to improving policy formulations that address illegal mining and its associated impacts on the environment and local economie